Find all real numbers such that

$$\sqrt{x-\frac{1}{x}} + \sqrt{1 - \frac{1}{x}} = x$$

My attempt to the solution :

I tried to square both sides and tried to remove the root but the equation became of 6th degree.Is there an easier method to solve this?

  • $\begingroup$ rewriting it as? $\endgroup$ – maths lover Jul 7 '13 at 22:07
  • $\begingroup$ @rattanjot: Are you sure you write the signs inside the radicals correctly? $\endgroup$ – Amzoti Jul 7 '13 at 22:09
  • $\begingroup$ ya sure its correct. $\endgroup$ – maths lover Jul 7 '13 at 22:11

Let's multiply $$ \sqrt{x-1/x} + \sqrt{1 - 1/x} = x\tag{1} $$ by $(\sqrt{x-1/x} - \sqrt{1 - 1/x})$. Then we get $$ x-1=x(\sqrt{x-1/x} - \sqrt{1 - 1/x}) $$ $$ \sqrt{x-1/x} - \sqrt{1 - 1/x}=1-1/x\tag{2} $$ Sum up $(1)$ and $(2)$ to get $$ 2\sqrt{x-1/x}=x-1/x+1 $$ Now make the substitution $y=\sqrt{x-1/x}$. The rest is clear.


Multiply with $\sqrt{x-1/x}-\sqrt{1-1/x}$ to get $$x-1=(x-\frac1x)-(1-\frac1x) =x\left(\sqrt{x-1/x}-\sqrt{1-1/x}\right)$$ so $$1-\frac1x = \sqrt{x-1/x}-\sqrt{1-1/x}$$ and by adding $$ x+1-\frac1x =2\sqrt{x-\frac1x}$$ Now with $z=x-\frac1x$, this is simply $$z+1=2\sqrt z,$$ a quadratic in $\sqrt z$ with (double) solution $\sqrt z=1$, so $z=1$ and we need to solve $$ x-\frac1x=1$$ i.e. $$ x^2-x-1=0.$$ This has solutions $x=\frac{1\pm\sqrt 5}2$, but only the positive value is possible.

  • 1
    $\begingroup$ Norbert got the same solution just a bit earlier. $\endgroup$ – dfeuer Jul 7 '13 at 22:13
  • $\begingroup$ foiled again :) $\endgroup$ – Hagen von Eitzen Jul 7 '13 at 22:14
  • 1
    $\begingroup$ Nice $\varphi$ solution there. $\endgroup$ – Constantine Jul 7 '13 at 23:16


$$x=\sqrt{x-\frac1x}+\sqrt{1-\frac1x}\implies x\sqrt x=\sqrt{x^2-1}+\sqrt{x-1}\implies$$

$$ x^3=x^2+x-2+2\sqrt{x^3-x^2-x+1}\implies(x^3-x^2-x+2)^2=4(x^3-x^2-x+1)$$

Well, now you can put $\,w:=x^3-x^2-x+1\;$ and solve

$$(w+1)^2=4w\iff (w-1)^2=0\iff w=1\;\ldots\;\text{and etc.}\ldots$$


Clearly, $x\ne0$

$$\sqrt{x-1/x} + \sqrt{1 - 1/x} = x$$

$$\implies \sqrt{x^2-1}+\sqrt{x-1}=x\sqrt x$$

$$\implies \sqrt{x-1}(\sqrt{x+1}+1)=x\sqrt x$$

$$\implies \sqrt{x-1}\frac{x+1-x}{\sqrt{x+1}-1}=x\sqrt x\text{ (rationalizing the numerator) }$$

$$\implies \sqrt{x-1}=\sqrt x(\sqrt{x+1}-1)=\sqrt{x^2+x}-\sqrt x$$

$$\implies \sqrt x+ \sqrt{x-1}=\sqrt x(\sqrt{x+1}-1)=\sqrt{x^2+x}$$

Squaring we get, $$x+x-1+2\sqrt{x^2-x}=x^2+x\iff 2\sqrt{x^2-x}=x^2-x+1$$

Putting $x^2-x=a^2,a^2=2a-1\implies (a-1)^2=0\implies a=1$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.